Physical-biological interactions in the Northern Humboldt Upwelling Current System and the consequences to the absorption of carbon - Aburto, Rodrigo Mogollón (2019)
It has been hypothesized that global warming will strengthen upwelling-favorable winds in the Northern Humboldt Current System (NHCS) as a consequence of the increase of the land-sea thermal gradient along the Peruvian coast. The effect of strengthened winds in this region is assessed with the use of a coupled physical-biogeochemical model forced with projected and climatological winds. Strengthened winds induce an increase in primary production of 2% per latitudinal degree from 9.5∘S to 5∘S. In some important coastal upwelling sites primary production is reduced. This is due to a complex balance between nutrient availability, nutrient use efficiency, as well as eddy- and wind-driven factors. Mesoscale activity induces a net offshore transport of inorganic nutrients, thus reducing primary production in the coastal upwelling re-gion. Wind mixing, in general disadvantageous for primary producers, leads to shorter residence times in the southern and central coastal zones. Overall, instead of a propor-tional enhancement in primary production due to increased winds, the NHCS becomes only 5% more productive (+5 mol C m−2 year−1), 10% less limited by nutrients and 15% less efficient due to eddy-driven effects. It is found that regions with an initial strong nutrient limitation are more efficient in terms of nutrient assimilation which makes them more resilient in face of the acceleration of the upwelling circulation. We use the same coupled physical–biogeochemical model to investigate the drivers and mechanisms responsible for the spatiotemporal variability of the partial pressure of carbon dioxide in seawater (pCO2) and associated air–sea CO2 fluxes in the NHCS. Simulated pCO2 is in good agreement with available observations with an average absolute error of, approximately, 24 atm. The highly productive upwelling region, 300 km from the shore and between 5 and 17∘S, is shown to be a strong CO2 source with an averaged flux of 5.60 ± 2.94 mol C m−2 year−1, which represents an integrated carbon flux of 0.028 ± 0.015 Pg C year−1. Through a series of model experiments we show that the high pCO2 is primarily the result of coastal upwelling, which is incompletely compensated by biology. Specifically, the supply of dissolved inorganic carbon (DIC)-rich waters to the surface pushes pCO2 up to levels around 1100 atm. Even though biological production is high, it reduces pCO2 only by about 300 atm. We show that this relatively low degree of biological compensation, which implies an inefficient biological pump in the nearshore domain, results from a spatio-temporal de-coupling between the counteracting effects of biological production and the transport and mixing of DIC. The contribution of the outgassing and the processes affecting CO2 solubility, associated with the seasonal cycle of heating and cooling, are minor. Across the whole domain, the balance of mechanisms is similar, but with smaller amplitudes. We demonstrate that seawater pCO2 is more sensitive to changes in DIC and sea surface temperature, while alkalinity plays a minor role. The role played by El Niño-Southern Oscillation (ENSO) on modulating the oceanic carbon emittance is assessed. pCO2 was inferred from a recent neural network methodology forced with outputs from a coupled physical-biogeochemical hindcast, which permits to reconstruct the interannual variability of pCO2 and associated air-sea CO2 fluxes from 1998 through 2015 at monthly timescales. Results show a large spatiotemporal variability of the CO2 exchange to nine El Niño and La Niña episodes throughout the period of analysis and within the coastal and equatorial upwelling region that variability results from combined ENSO-driven pCO2 and wind speed variations. It is found that the relatively weak CO2 source behavior during an average Niño episode is mainly caused by a decrease of pCO2 which is partially compensated by more efficient gas exchange at the air-sea interface due to the strengthening of the upwelling-favorable winds, therefore increasing the CO2 transfer velocity. Conversely, the strong CO2 source behavior during an average La Niña episode results from more efficient upwelling which brings colder and CO2-rich waters to the surface, thus increasing pCO2 and the associated CO2 efflux. Moreover, it is estimated that during an average El Niño episode the total amount of carbon retained within the coastal and equatorial upwelling region in the NHCS is about half a million metric tons of carbon that normally would have been lost to the atmosphere as CO2. In contrast, during an average La Niña episode, one million metric tons of carbon is additionally emitted, largely contributing to the atmospheric CO2 accumulation.